2020
DOI: 10.1029/2020jd033220
|View full text |Cite
|
Sign up to set email alerts
|

A More Important Role for the Ozone‐S(IV) Oxidation Pathway Due to Decreasing Acidity in Clouds

Abstract: Clouds significantly affect the Earth's radiation budget and play a critical role in atmospheric sulfate formation. The pathways of S(IV) oxidations have recently caused a controversial attention under severe haze episodes due to the variable acidity and water content in aerosol particles. In this study, a total of 158 cloud samples were collected from 2014 to 2018 at the summit of Mt. Tai, China, to explore the roles of atmospheric oxidants in aqueous S(IV) oxidation. The results showed that the averaged pH v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…A recent study reported an increasing trend of H 2 O 2 concentrations in the cloud samples at the summit of Mt. Tai from 2014 to 2018 (Li et al, 2020)…”
Section: Comparison With Previous Studiesmentioning
confidence: 98%
“…A recent study reported an increasing trend of H 2 O 2 concentrations in the cloud samples at the summit of Mt. Tai from 2014 to 2018 (Li et al, 2020)…”
Section: Comparison With Previous Studiesmentioning
confidence: 98%
“…As a consequence, the increased aqueous-phase partitioning enables higher chemical processing rates of weak acids such as SO2, HONO and organic carboxylic acids. Both lower acidity and stronger buffering can support faster S(IV) to S(VI) conversions due to the higher efficiency of other chemical pathways such as ozone oxidation (Li et al, 2020b) and therefore reduce the tropospheric lifetime (and incloud lifetime) of SO2. Therefore, under future conditions with a lower overall SO2 budget, the increased secondary sulfate mass formation probabilities may compensate at least partly the reduced sulfate formation potential.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…Total column SO 2 (TCSO 2 ) measurements came from the Ozone Monitoring Instrument (OMI), which were obtained from the Goddard Earth Sciences Data and Information Services Centre (https://aura.gesdisc.eosdis.nasa.gov/data/Aura_OMI_Level2/ OMSO2.003) (Li et al, 2020). OMI is situated on-board NASA's polar-orbiting Aura satellite launched in 2004 with a local overpass time of approximately 13:45.…”
Section: Satellite Observationsmentioning
confidence: 99%
“…Of these, the satellite data sets with the best temporal resolution and spatial coverage for SO 2 are from the Ozone Monitoring Instrument aboard the NASA Earth Observing System Aura spacecraft (Fioletov et al, 2016). Although biases in the SO 2 retrieval from OMI limit its use at high and low latitudes in winter and over ares with low atmospheric loading, they do provide valuable information over regions where there are no long term, or even any ground-based observations (Li et al, 2020;Levelt et al, 2018). This paper is configured as follows; the model (UKESM1), the model simulations, observation data sets and modifications to UKESM1's SO 2 dry deposition parameterization are described in Section 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation